Pergerakan kamera boleh mewakili watak - Sigar., Justine Harold Sebastian (Universiti Malaysia Sarawak (UNIMAS), 2007)
Camera movements are technically applied in filmmaking to enhance the visual storytelling It represents the director's intuitive interpretation of events in the story apart ;rom creating a dynamic and three-dimensional Image on screen. Generally camera movements include static and non-static movement. In a short film entitled Pant!, camera movements are care/tilly applied to represent the event as seen through the character's perspective.